Structural controls and hydrogeochemical properties of geothermal fields in the Varto region, East Anatolia - Uzelli, Taygun; Sener, Mehmet Furkan; Dolek, Iskender; Baba, Alper; Sozbilir, Hasan; Dirik, Ramazan Kadir (Scientific Technical Research Council Turkey-Tubitak, 2021)
Varto and the surrounding region have important geothermal fields, developing in strike-slip tectonic setting in East Anatolia, which resulted from the collision of the Arabian and Eurasian plates. The main structural elements in the area are the NE-trending sinistral and NW-trending dextral strike-slip fault segments and N-S trending extension zones. In order to determine fault-controlled geothermal circulation, it is very important to fully characterize the structural elements in these complex environments. The widely distributed volcanic rocks have fracture and crack systems that play an important role in surface infiltration, geothermal fluid, and groundwater circulation. Especially in areas where the fault segments intersect, hot springs outlets and natural resources easily come to the surface. In order to understand the flow paths of geothermal fluid along the faults in these geothermal systems, it is necessary to determine the stress state of the faults and to map the distribution of the structural elements. For this reason, we conducted a detailed study on the Varto Fault Zone, which has important geothermal fields in Eastern Anatolia. We present conceptual models of the geothermal fields in the Varto region that show favorable geothermal activity on the intersecting fault segments, fault bends, step-overs, and accompanying fracture-crack sets. As a result, we emphasize that the planes of strike-slip faults in transtensional areas are more favorable for secondary permeability and enhances the geothermal fluid circulation, and this can be supported by hydrogeochemical data.
Keywords: Structural geology; Eastern Anatolia; geothermal energy; Varto; triple junction; North Anatolian Fault; Geochemical Features; Eastern Anatolia; Volcanic-Rocks; Turkey; Earthquake; Evolution; Deformation; Initiation; Inversion